Increased Survival of Antibiotic-Resistant Escherichia coli inside Macrophages - Miskinyte, M. (2015)
Mutations causing antibiotic resistance usually incur a fitness cost in the absence of antibiotics. The magnitude of such costs is known to vary with the environment. Little is known about the fitness effects of antibiotic resistance mutations when bacteria confront the host's immune system. Here, we study the fitness effects of mutations in the rpoB, rpsL, and gyrA genes, which confer resistance to rifampin, streptomycin, and nalidixic acid, respectively. These antibiotics are frequently used in the treatment of bacterial infections. We measured two important fitness traits-growth rate and survival ability-of 12 Escherichia coli K-12 strains, each carrying a single resistance mutation, in the presence of macrophages. Strikingly, we found that 67% of the mutants survived better than the susceptible bacteria in the intracellular niche of the phagocytic cells. In particular, all E. coli streptomycin-resistant mutants exhibited an intracellular advantage. On the other hand, 42% of the mutants incurred a high fitness cost when the bacteria were allowed to divide outside of macrophages. This study shows that single nonsynonymous changes affecting fundamental processes in the cell can contribute to prolonged survival of E. coli in the context of an infection.